Heat transfer suppressing sheet and battery pack
By using heat transfer inhibitors composed of inorganic fibers and liquid repellent substances in the battery pack, the thermal runaway problem caused by expansion and contraction of the battery cell is solved, and the immersion of dew condensation and electrolyte is prevented, and thermal insulation and insulation are achieved. The maintenance of the battery cells avoids short circuits and fires.
Patent Information
- Application Number
- CN202380049524.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-06-27
- Filing Date
- 2023-06-26
- Publication Date
- 2025-02-11
AI Technical Summary
The thermal runaway caused by expansion and contraction during the charging and discharging of the battery cells may cause the formation of dew condensation and the insulation of the thermal insulation material to decrease, which will lead to short circuits and fires between the battery cells.
Using a heat transfer inhibiting sheet containing inorganic fibers and a liquid repellent substance with a smaller surface tension than water, the heat transfer inhibiting sheet is prevented from immersion of dew condensation and electrolyte, thereby maintaining heat insulating. and prevent short circuits and fires.
It effectively suppresses the reduction of insulation and thermal insulation of the heat transfer suppressor sheet, prevents short circuits and fires between battery cells, and improves the safety of the battery pack.
Smart Images

Figure CN119422271A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a heat transfer suppressing sheet and a battery pack having the same. Background Art
[0002] In recent years, from the perspective of environmental protection, electric vehicles and hybrid vehicles driven by electric motors have been actively developed. These electric vehicles and hybrid vehicles are equipped with a battery pack composed of a plurality of battery cells connected in series or in parallel to serve as a power source for the driving electric motor.
[0003] In addition, lithium-ion secondary batteries are mainly used in the battery cells, which have higher capacity and higher output than lead-acid batteries, nickel-metal hydride batteries, etc. Moreover, in the case of thermal runaway, such as a battery cell rapidly heating up and then continuously releasing heat due to internal short circuit, overcharging, etc. of the battery, the heat from the battery cell that has thermal runaway is transmitted to other adjacent battery cells, which may cause thermal runaway of other battery cells.
[0004] As a method of suppressing the spread of fire from a battery cell that has undergone thermal runaway as described above, a method of arranging a heat insulating material between battery cells is generally used.
[0005] For example, Patent Document 1 discloses a thermal insulation material having a composite layer including fiber sheets and silica aerogel, wherein the fiber sheets are stacked in a folded manner. Patent Document 1 states that the thermal insulation sheet can follow the change in the gap between battery cells due to the expansion and contraction of the battery cells.
[0006] Prior art literature
[0007] Patent Literature
[0008] Patent Document 1: Japanese Patent Application Publication No. 2021-34278 Summary of the invention
[0009] Problems to be solved by the invention
[0010] In addition, in existing battery packs (battery cells), during the charge and discharge of battery cells, as the battery cells expand and contract, heat release and cooling will occur repeatedly, so condensation water may be generated inside the battery shell. And if the generated condensation water seeps into the insulation material, the insulation of the insulation material will be reduced, and adjacent battery cells will short-circuit each other, which may cause fire. In addition, in the case where a battery cell is damaged due to thermal runaway, if the electrolyte inside the battery cell seeps into the insulation material at high temperature, the insulation of the insulation material will be significantly reduced, which will become a chain reaction causing thermal runaway.
[0011] The heat insulating material described in Patent Document 1 cannot prevent a decrease in insulation due to the infiltration of condensation water and a decrease in heat insulating properties due to the infiltration of an electrolyte solution.
[0012] The present invention has been completed in view of the above-mentioned problems, and its purpose is to provide a heat transfer suppression sheet and a battery pack having the heat transfer suppression sheet, wherein the heat transfer suppression sheet has excellent thermal insulation properties and can prevent the infiltration of moisture, thereby preventing fire caused by short circuits between battery cells, and preferably preventing a reduction in thermal insulation properties due to the infiltration of electrolyte.
[0013] Means for solving problems
[0014] The above object of the present invention is achieved by the following configuration [1] of the heat transfer suppressing sheet.
[0015] [1] A heat transfer suppression sheet interposed between a plurality of battery cells, characterized in that the heat transfer suppression sheet comprises: at least one fiber selected from inorganic fibers and organic fibers; and a liquid-repellent material having a surface tension smaller than that of water.
[0016] In addition, preferred embodiments of the heat transfer suppressing sheet of the present invention relate to the following [2] to
[12] .
[0017] [2] The heat transfer suppressing sheet according to [1], comprising inorganic particles, wherein at least a part of the inorganic particles is the liquid repellent substance.
[0018] [3] The heat transfer suppressing sheet according to [2], wherein the liquid repellent substance is hydrophobic silica.
[0019] [4] The heat transfer suppressing sheet according to [1], characterized in that
[0020] The heat transfer suppressing sheet comprises inorganic particles,
[0021] The liquid repellent substance adheres to at least a part of the surface of the heat transfer suppression sheet, the surface of the inorganic particles inside the heat transfer suppression sheet, and the surface of the fibers inside the heat transfer suppression sheet.
[0022] [5] The heat transfer suppression sheet as described in [4] is characterized in that the above-mentioned liquid repellent substance is at least one selected from paraffin base oils, cycloparaffin base oils, hydrocarbon synthetic oils, ester synthetic oils, animal and plant oils and fats, silicone resins and fluororesins, rosin-based sizing agents and alkyl ketene dimer sizing agents.
[0023] [6] The heat transfer suppression sheet described in [4] or [5] is characterized in that the inorganic particles are particles composed of at least one inorganic material selected from oxide particles, carbide particles, nitride particles and inorganic hydrate particles.
[0024] [7] The heat transfer suppressing sheet according to [6], wherein the inorganic particles include at least one particle selected from dry silica particles and silica aerogel.
[0025] [8] The heat transfer suppressing sheet described in [7] is characterized in that the inorganic particles further contain particles of at least one selected from the group consisting of titanium dioxide, zircon, zirconium oxide, silicon carbide, zinc oxide, and aluminum oxide.
[0026] [9] The heat transfer suppression sheet according to any one of [1] to [8], wherein the surface tension of the liquid repellent substance is smaller than the surface tension of the electrolyte contained in the battery cell.
[0027]
[10] The heat transfer suppressing sheet according to any one of [1] to [9], wherein the surface tension of the liquid repellent substance is 45 mN / m or less.
[0028]
[11] The heat transfer suppressing sheet described in
[10] , wherein the liquid repellent substance is at least one selected from silicone resins and fluororesins.
[0029]
[12] The heat transfer suppressing sheet according to any one of [1] to
[11] , characterized in that
[0030] The heat transfer suppression sheet has a plurality of three-dimensionally connected pores.
[0031] The pores are open toward the surface of the heat transfer suppressing sheet.
[0032] In addition, the above-mentioned object of the present invention is achieved by the following
[13] structure of the battery pack.
[0033]
[13] A battery pack comprising a plurality of battery cells and the heat transfer suppressing sheet according to any one of [1] to
[12] , wherein the plurality of battery cells are connected in series or in parallel.
[0034] Effects of the Invention
[0035] The heat transfer suppression sheet of the present invention has a liquid-repellent substance on at least a portion of the surface and the interior thereof. The surface tension of the liquid-repellent substance is smaller than the surface tension of water, and thus it is possible to suppress the penetration of condensation water or the like generated on the exterior of the heat transfer suppression sheet into the interior of the heat transfer suppression sheet. Therefore, it is possible to suppress the reduction in insulation of the heat transfer suppression sheet, the short circuit between adjacent battery cells, and the ignition of the battery cells. In addition, if the surface tension of the liquid-repellent substance is smaller than the surface tension of the electrolyte used in the battery cells, it is also possible to suppress the penetration of the electrolyte into the interior of the heat transfer suppression sheet, and it is possible to prevent the reduction in thermal insulation.
[0036] The battery pack of the present invention has a heat transfer suppression sheet having excellent thermal insulation properties and suppressing the penetration of condensation water or electrolyte as described above, thereby preventing short circuits between battery cells in the battery pack, suppressing thermal runaway of the battery cells, and suppressing the spread of flames to the outside of the battery case. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] Figure 1 This is a schematic cross-sectional view showing the structure of a heat transfer suppression sheet according to a first embodiment of the present invention.
[0038] Figure 2 This is a cross-sectional view schematically showing a battery pack including the heat transfer suppression sheet according to the first embodiment of the present invention.
[0039] Figure 3 This is a schematic cross-sectional view showing the structure of a heat transfer suppression sheet according to a second embodiment of the present invention.
[0040] Figure 4 This is a photograph in place of a drawing showing a cross section of a heat insulating material that can be used in the heat transfer suppressing sheet according to the embodiment of the present invention.
[0041] Figure 5 This is a schematic cross-sectional view showing a structure in which the heat transfer suppression sheet according to the second embodiment has three-dimensionally connected pores.
[0042] Figure 6 This is a schematic cross-sectional view showing a state in which the heat transfer suppression sheet according to the second embodiment is arranged adjacent to a battery cell. DETAILED DESCRIPTION
[0043] The present inventors have conducted intensive studies on a heat transfer suppressing sheet that can solve the above-mentioned problems.
[0044] As a result, it was found that by adding a liquid repellent substance to the surface of the heat transfer suppression sheet or adding a liquid repellent substance inside the sheet, and using a substance having a surface tension smaller than that of water as the liquid repellent substance, it is possible to prevent condensation water generated outside the heat transfer sheet from entering the sheet. In addition, when the heat transfer sheet is arranged near a battery cell, for example, if a substance having a surface tension smaller than that of the electrolyte filled in the battery cell is used as the liquid repellent substance, it is possible to prevent the electrolyte leaking from the battery cell from entering the heat transfer suppression sheet, and to prevent a decrease in thermal insulation.
[0045] The heat transfer suppression sheet, its manufacturing method and battery pack according to the embodiment of the present invention are described in detail below. It should be noted that the present invention is not limited to the embodiment described below, and can be implemented with any modifications within the scope of the present invention.
[0046] [Heat transfer suppression sheet]
[0047] <First Embodiment>
[0048] Figure 1 : is a schematic cross-sectional view showing the structure of the heat transfer suppression sheet according to the first embodiment of the present invention. Figure 2 This is a cross-sectional view schematically showing a battery pack including the heat transfer suppression sheet according to the first embodiment of the present invention.
[0049] like Figure 1 As shown, the heat transfer suppression sheet 10 of this embodiment has a liquid repellent substance 2 attached to the surface of the heat insulating material 9. The heat insulating material 9 has nano-silicon dioxide 4 and titanium dioxide 3 as inorganic particles, and has glass fiber 1 as fiber. It should be noted that the liquid repellent substance 2 is a substance having a surface tension smaller than that of water, such as a rosin-based sizing agent.
[0050] As a specific use of the heat transfer suppression sheet 10, Figure 2 As shown, the heat transfer suppression sheet 10 can be sandwiched between multiple battery cells 20a, 20b, 20c. And the multiple battery cells 20a, 20b, 20c are stored in the battery case 30 in a state of being connected in series or in parallel (the connected state is omitted in the figure), forming a battery pack 100. It should be noted that the battery cells 20a, 20b, 20c are suitable for use as lithium ion secondary batteries, but are not particularly limited to this, and can also be applied to other secondary batteries.
[0051] In the battery pack 100 configured as described above, the temperature of the battery cells 20a, 20b, 20c rises during operation (charge and discharge), and the temperature inside the battery case 30 also rises. Thereafter, when the operation of the battery pack 100 is stopped and the air inside the battery case 30 is cooled, condensation water adheres to the battery cells 20a, 20b, 20c and the inner surface of the battery case 30.
[0052] At this time, in the heat transfer suppression sheet 10 of the first embodiment, the liquid repellent material 2 having a surface tension smaller than that of water is attached to the surface thereof, and the liquid repellent material 2 has a property of repelling water, thereby being able to suppress the infiltration of the condensation water 5 into the heat transfer suppression sheet 10. Therefore, it is possible to suppress the reduction in the insulation property of the heat transfer suppression sheet, and to prevent the adjacent battery cells, for example, the battery cells 20a and 20b from short-circuiting or catching fire.
[0053] In addition, in the battery pack 100, for example, when the battery cell 20c swells and breaks due to thermal runaway, and the electrolyte filled in the battery cell 20c flows out, if the electrolyte penetrates into the insulation material at high temperature, the insulation of the insulation material will be significantly reduced, which will cause a chain reaction of thermal runaway. In such a case, if, for example, fluororesin is used as the liquid-repellent material 2, the fluororesin has a surface tension smaller than the surface tension of the electrolyte (for example, dimethyl carbonate (DMC)) filled in the battery cells 20a, 20b, 20c. Therefore, the liquid repellency is exerted not only against the condensation water 5 but also against the electrolyte, and the electrolyte can be suppressed from penetrating into the heat transfer suppression sheet 10, and the chain reaction of thermal runaway can be prevented.
[0054] In the first embodiment, when the heat transfer suppression sheet 10 has the liquid repellent material 2 on its surfaces 10a, 10b, if the liquid repellent material 2 is attached to at least a portion of the surfaces 10a, 10b, the effect of preventing condensation water or electrolyte from intruding into the heat transfer suppression sheet 10 can be obtained compared to the case where the liquid repellent material 2 is not attached. However, it is preferable that the liquid repellent material 2 is attached so as to completely cover the entire surface of the surfaces 10a, 10b. When the liquid repellent material 2 is attached to the entire surface of the surfaces 10a, 10b of the heat transfer suppression sheet 10 in this way, the intrusion of condensation water or electrolyte into the heat transfer suppression sheet 10 can be reliably prevented. The manufacturing method of the heat transfer suppression sheet 10 of the first embodiment is as follows.
[0055] In addition, the heat transfer suppressing sheet 10 of the present embodiment has the glass fiber 1, which is an inorganic fiber, as the fiber. Therefore, the glass fiber 1 functions as an aggregate of the heat transfer suppressing sheet 10, and a high compressive strength can be obtained. Figure 2As shown, the heat transfer suppression sheet 10 of this embodiment is sandwiched between a plurality of battery cells 20a, 20b, 20c, but the battery cells 20a, 20b, 20c arranged adjacent to the heat transfer suppression sheet 10 may expand or contract due to charging and discharging, etc. At this time, since the heat transfer suppression sheet 10 has high compressive strength, even if the battery cells 20a, 20b, 20c are squeezed, they will not be significantly deformed and can maintain their shape. Therefore, it is possible to prevent the reduction in thermal insulation due to the thickness of the heat transfer suppression sheet 10 becoming thinner due to compression or the inorganic particles, etc. falling off from the heat transfer suppression sheet 10. In addition, since the inorganic fiber has high high temperature strength, it is possible to maintain its shape even when the heat transfer suppression sheet 10 is exposed to high temperatures.
[0056] Furthermore, the heat transfer suppressing sheet 10 of the present embodiment contains the nano-silica 4 and the titanium dioxide 3 as inorganic particles. Since these inorganic particles can exhibit thermal insulation properties in a wide temperature range, excellent thermal insulation properties can be obtained.
[0057] <Second Embodiment>
[0058] Figure 3 2 is a schematic cross-sectional view showing the structure of a heat transfer suppression sheet according to a second embodiment of the present invention. In the heat transfer suppression sheet 10 of the first embodiment, the liquid repellent material 2 is attached to the surface of the heat insulating material 9, but in the second embodiment, the attachment area of the liquid repellent material 2 is different from that in the first embodiment. However, the second embodiment is the same as the first embodiment in terms of other materials, etc., so Figure 3 In Figure 1 The same parts are denoted by the same reference numerals, and their detailed description is omitted.
[0059] like Figure 3 As shown, the heat transfer suppressing sheet 10 of the second embodiment has a so-called internal addition type structure in which the liquid repellent substance 2 is attached to at least a part of the surface of the fibers (glass fibers 1) and inorganic particles (nanosilica 4 and titanium dioxide 3) inside the heat insulating material 9.
[0060] Since the liquid repellent material 2 is added to the heat transfer suppression sheet 10 of the second embodiment configured as described above, although the condensation water 5 or the electrolyte penetrates to a certain depth from the surfaces 10a, 10b, it is possible to prevent the complete penetration. Therefore, it is possible to suppress the reduction in the insulation of the heat transfer suppression sheet, prevent fire caused by short circuits between adjacent battery cells, and prevent the reduction in thermal insulation caused by the penetration of high-temperature electrolyte.
[0061] Furthermore, as shown in the second embodiment, if the liquid repellent substance 2 is added to the heat transfer suppression sheet 10, even if the surfaces 10a and 10b of the heat transfer suppression sheet 10 are damaged, the infiltration of the condensation water 5 can be prevented in the middle.
[0062] It should be noted that, as shown in the second embodiment, the liquid-repellent substance 2 is attached to at least a portion of the surface of the fibers (glass fibers 1) and inorganic particles (nano-silicon dioxide 4 and titanium dioxide 3) inside the insulating material 9, and as shown in the first embodiment, the liquid-repellent substance 2 is attached to the surface of the insulating material 9, thereby obtaining a heat transfer suppression sheet having the excellent effects of both.
[0063] <Third Embodiment>
[0064] Regarding the third embodiment, illustration is omitted and reference is made to Figure 1 The heat transfer suppression sheet 10 of the third embodiment is not Figure 1 In the heat insulating material 9, liquid repellent material 2 is attached to the surface, and liquid repellent inorganic particles are used. That is, at least a part of the inorganic particles in the heat insulating material 9 is liquid repellent. Examples of such inorganic particles include hydrophobic silica (fumed silica).
[0065] In the third embodiment thus configured, since the liquid-repellent inorganic particles are also present on the surface, the intrusion of the condensation water 5 into the interior can be easily prevented without performing a step of attaching the liquid-repellent substance 2 to the surface of the heat transfer suppressing sheet 10 .
[0066] It should be noted that, when the heat transfer suppression sheet 10 is manufactured using only inorganic particles composed of the liquid repellent substance 2 without including at least one fiber selected from inorganic fibers and organic fibers, if the condensation water 5 penetrates into the interior of the heat transfer suppression sheet 10, the inorganic particles will agglomerate with each other and cracks will be easily generated. In this embodiment, since the fiber (glass fiber 1) is included, the agglomeration of the inorganic particles can be suppressed, and the generation of cracks can be prevented.
[0067] Next, the heat insulating material that can be used in the heat transfer suppression sheet according to the embodiment of the present invention will be described in more detail. Figure 4 This is a photograph in place of a drawing showing a cross section of a heat insulating material that can be used in the heat transfer suppressing sheet according to the embodiment of the present invention. Figure 4The heat insulating material 19 shown includes inorganic particles 14 and organic fibers 6. As the inorganic particles 14, nano-silicon dioxide, titanium dioxide, etc. can be used, as shown in the first and second embodiments above. In addition, as the organic fiber 6, polyethylene terephthalate (PET: Polyethyleneterephthalate) fiber, etc. can be used. In addition, as shown in the first and second embodiments above, inorganic fibers such as glass fibers 1 may also be included.
[0068] The heat insulating material 19 may have a plurality of three-dimensionally connected pores 7 between the inorganic particles 14 and between the inorganic particles 14 and the organic fibers 6. At least a portion of the pores 7 communicate with the surface 19a of the heat insulating material 19 and have openings 7a that open outward.
[0069] like Figure 4 As shown, the inorganic particles 14 are exposed on the surface 19a of the heat insulating material 19 used in this embodiment, forming extremely fine irregularities, so that the heat insulating material 19 itself has a water-repellent structure. In addition, in the first and second embodiments, the liquid-repellent substance is attached to the surface 19a of the heat insulating material 19, or the liquid-repellent substance is attached to the inorganic particles 14 and the surface of the organic fiber 6 inside the heat insulating material, and in the third embodiment, inorganic particles composed of a liquid-repellent substance are used. Therefore, compared with the case where the liquid-repellent substance is applied to the heat insulating material that does not contain a predetermined amount of inorganic particles and does not form fine irregularities on the surface, the effect of preventing the infiltration of condensation water and electrolyte can be significantly improved.
[0070] It should be noted that if Figure 4 As shown in FIG. 1 , if the heat insulating material 19 has three-dimensionally connected pores 7, and the pores 7 have openings 7a, when a liquid repellent substance is applied from the surface side of the heat insulating material 19, the liquid repellent substance easily penetrates into the inside of the heat insulating material 19 through the openings 7a. In particular, when hydrophobic silica is used as the inorganic particles 14, if it is desired to further attach the liquid repellent substance from the surface of the heat insulating material 19, the inorganic particles 14 may exert their liquid repellency and may be difficult to attach. In contrast, Figure 4 As shown, if the heat insulating material 19 has the pores 7 having the openings 7 a , the liquid repellent substance can easily penetrate into the heat insulating material 19 , thereby improving the liquid repellency.
[0071] Figure 5 This is a schematic cross-sectional view showing the structure of the heat transfer suppression sheet according to the second embodiment described above when it has three-dimensionally connected pores. Figure 6 This is a schematic cross-sectional view showing a state where the heat transfer suppression sheet according to the second embodiment is arranged adjacent to a battery cell.
[0072] like Figure 5As shown, if the heat transfer suppression sheet 10 has three-dimensionally connected pores 7, and the pores 7 have openings 7a, a water inlet / drainage passage 8 is formed that communicates the openings 7a with the pores 7. Therefore, even if the condensation water 5 infiltrates into the heat transfer suppression sheet 10 from the openings 7a of the pores 7 or other parts, the condensation water 5 can be discharged to the outside through the water inlet / drainage passage 8.
[0073] In addition, if Figure 6 As shown in FIG. 1 , when the temperature of the battery cell 20c rises during operation, the temperature of the heat transfer suppression sheet 10 also rises to a certain extent, and the moisture inside the heat transfer suppression sheet 10 evaporates and becomes water vapor, which can be discharged to the outside through the water inlet / outlet passage 8. In addition, when the battery cell 20c expands during operation, the battery cell 20c and the heat transfer suppression sheet 10 are Figure 6 The interval between the battery cells 20b (not shown) is narrowed, and the heat transfer suppressing sheet 10 is pressed. At this time, if water penetrates into the heat transfer suppressing sheet 10, the condensed water 5 is easily discharged through the water inlet / drainage passage 8.
[0074] The materials constituting the heat transfer suppressing sheet of the present embodiment will be described in detail below.
[0075] <Liquid repellent substances>
[0076] The liquid repellent material 2 is an important component that has the effect of preventing the condensation water 5 from infiltrating into the heat transfer suppression sheet 10. In order to prevent the infiltration of the condensation water 5, the surface tension of the liquid repellent material 2 needs to be smaller than the surface tension of water. In addition, if the surface tension is made smaller than that of the electrolyte contained in the battery cell arranged near the heat transfer suppression sheet 10, the infiltration of the electrolyte can also be prevented.
[0077] Since the surface tension of water at 25°C is about 72.0 (mN / m), the specific value of the surface tension of the liquid repellent substance is, for example, 70.0 (mN / m) or less, preferably 65 (mN / m) or less. In order to suppress the infiltration of the electrolyte, the surface tension of the liquid repellent substance is more preferably 45 (mN / m) or less, and further preferably 25 (mN / m) or less.
[0078] Examples of the liquid repellent substance include commonly used water repellents, oil repellents, and sizing agents.
[0079] Specific examples of water repellents include paraffin base oils, cycloparaffin base oils, hydrocarbon synthetic oils, ester synthetic oils, animal and plant oils and fats. Specific examples of oil repellents include silicone resins and fluororesins. Specific examples of sizing agents include rosin (rosin), alkyl ketene dimer (AKD: Alkyl Ketene Dimer), etc.
[0080] Among these liquid repellent substances, silicone resin and fluororesin are examples of liquid repellent substances having a surface tension smaller than that of the electrolyte. It should be noted that the surface tension of silicone resin is 16 to 30 (mN / m), and the surface tension of fluororesin is 10 to 25 (mN / m).
[0081] As described in the third embodiment, inorganic particles may be used as the liquid repellent material. In this case, examples of the liquid repellent material include hydrophobic silica (fumed silica) and the like.
[0082] (Content of liquid repellent substances)
[0083] In the present embodiment, if the content of the liquid repellent material 2 relative to the total mass of the heat transfer suppressing sheet is appropriately controlled, sufficient liquid repellency with respect to the dew condensation water 5 and the electrolyte can be obtained.
[0084] The content of the liquid repellent substance 2 is preferably 5% by mass or more, and more preferably 10% by mass or more, relative to the total mass of the heat transfer suppression sheet 10. If the content of the liquid repellent substance 2 is too high, the content of the inorganic particles and fibers is relatively reduced. Therefore, in order to obtain the desired thermal insulation performance, the content of the liquid repellent substance 2 is preferably 35% by mass or less, and more preferably 20% by mass or less, relative to the total mass of the heat transfer suppression sheet 10.
[0085] <Inorganic particles>
[0086] As inorganic particles, single inorganic particles can be used, and more than two kinds of inorganic particles can also be used in combination. As the kind of inorganic particles, from the aspect of the heat transfer inhibition effect, preferably use the particles consisting of at least one inorganic material selected from oxide particles, carbide particles, nitride particles and inorganic hydrate particles, more preferably use oxide particles. In addition, there is no particular limitation on shape, preferably comprising at least one selected from nanoparticles, hollow particles and porous particles, specifically, inorganic hollow balls such as silicon dioxide nanoparticles, metal oxide particles, microporous particles, hollow silicon dioxide particles, particles consisting of thermally expansive inorganic materials, particles consisting of water-containing porous bodies, etc. can also be used.
[0087] If the average secondary particle size of the inorganic particles is 0.01 μm or more, it is easy to obtain and the increase in manufacturing cost can be suppressed. In addition, if it is 200 μm or less, the desired insulation effect can be obtained. Therefore, the average secondary particle size of the inorganic particles is preferably 0.01 μm or more and 200 μm or less, and more preferably 0.05 μm or more and 100 μm or less.
[0088] It should be noted that, if two or more kinds of inorganic particles with different heat transfer inhibition effects are used together, the exothermic body can be cooled in multiple stages, and endothermic effect can be shown in a wider temperature range. Specifically, it is preferred that large diameter particles and small diameter particles are mixed and used. For example, as shown in the first and second embodiments, when using nanoparticles (nano silicon dioxide 4) as inorganic particles on one side, inorganic particles as the other side preferably include inorganic particles (titanium dioxide 3) consisting of metal oxides. Hereinafter, the inorganic particles of small diameter are used as the first inorganic particles and the inorganic particles of large diameter are used as the second inorganic particles, and the inorganic particles are further described in detail.
[0089] <First Inorganic Particles>
[0090] (Oxide particles)
[0091] The refractive index of oxide particles is high, and the effect of diffuse reflection of light is strong. Therefore, when oxide particles are used as the first inorganic particles, radiative heat transfer can be suppressed, especially in high temperature areas such as abnormal heat release. As oxide particles, particles selected from at least one of silica, titania, zirconium oxide, zircon, barium titanate, zinc oxide and aluminum oxide can be used. That is, among the above-mentioned oxide particles that can be used as inorganic particles, only one type can be used, or two or more types of oxide particles can be used. In particular, silica is a component with high thermal insulation, and titania is a component with a higher refractive index than other metal oxides. It is highly effective in diffuse reflection of light and shielding radiant heat in high temperature areas above 500°C, so it is most preferred to use silica and titania as oxide particles.
[0092] (Average primary particle size of oxide particles: 0.001 μm or more and 50 μm or less)
[0093] The particle size of the oxide particles may affect the effect of reflecting radiant heat. Therefore, if the average primary particle size is limited to a predetermined range, a higher thermal insulation property can be obtained.
[0094] That is, if the average primary particle size of the oxide particles is greater than 0.001 μm, it is sufficiently larger than the wavelength of light that contributes to heating, so that the light is efficiently diffusely reflected. Therefore, in the high temperature region above 500°C, the radiation heat transfer in the heat transfer suppression sheet is suppressed, and the thermal insulation can be further improved.
[0095] On the other hand, if the average primary particle size of the oxide particles is less than 50 μm, the number of contacts between the particles will not increase even if compressed, making it difficult to form a path for conductive heat transfer. This can particularly reduce the impact on the insulation in the normal temperature range where conductive heat transfer dominates.
[0096] In the present invention, the average primary particle size can be determined by observing the particles with a microscope, comparing with a standard scale, and taking the average of any 10 particles.
[0097] (Nanoparticles)
[0098] In the present invention, nanoparticles refer to nano-scale particles with a spherical or nearly spherical average primary particle size of less than 1 μm. Since nanoparticles are low-density, conductive heat transfer can be suppressed. If nanoparticles are used as the first inorganic particles, the three-dimensionally connected pores 7 are further miniaturized, so excellent thermal insulation that suppresses convective heat transfer can be obtained. Therefore, when the battery is used in a normal temperature range, heat conduction between adjacent nanoparticles can be suppressed. From this aspect, nanoparticles are preferably used.
[0099] In addition, when nanoparticles with a small average primary particle size are used as oxide particles, even when the heat transfer suppression sheet is compressed due to expansion associated with thermal runaway of the battery cell and the internal density increases, the increase in conductive heat transfer of the heat transfer suppression sheet can be suppressed. It is believed that the reason for this is that nanoparticles easily form fine gaps between particles due to electrostatic repulsion, and the packing density is low, so the particles are filled in a manner having a buffering property.
[0100] Furthermore, if nanoparticles are included in the heat insulating material of the heat transfer suppression sheet 10 of the present embodiment, fine irregularities are formed on the surface of the heat insulating material, and thus the liquid repellency obtained by providing the liquid repellent substance 2 can be further improved as described above.
[0101] It should be noted that in the present invention, when nanoparticles are used as the first inorganic particles, there is no particular limitation on the material as long as it meets the above definition of nanoparticles. For example, silicon dioxide nanoparticles are highly thermally insulating materials, and the contact points between the particles are small, so the heat conducted by the silicon dioxide nanoparticles is less than that when using silicon dioxide particles with a large particle size. In addition, the bulk density of the silicon dioxide nanoparticles usually obtained is 0.1 (g / cm 3 ), so for example, even if the battery cells arranged on both sides of the heat transfer suppression sheet undergo thermal expansion and a large compressive stress is applied to the heat transfer suppression sheet, the size (area) and number of the contact points between the silica nanoparticles will not increase significantly, and the thermal insulation can be maintained. Therefore, as nanoparticles, silica nanoparticles are preferably used. Examples of silica nanoparticles include wet silica, dry silica, and aerogel, and silica nanoparticles particularly suitable for this embodiment are described below.
[0102] Generally, wet silica particles aggregate, whereas dry silica particles can be dispersed. In the temperature range below 300°C, heat conduction is dominant, so dry silica particles can be dispersed to obtain excellent thermal insulation performance compared to wet silica.
[0103] It should be noted that the heat transfer suppression sheet of this embodiment preferably uses a manufacturing method in which a mixture containing materials is processed into a sheet by a dry method. Therefore, as inorganic particles, dry silica, silica aerogel, etc. with low thermal conductivity are preferably used. In addition, it is also preferred to use hydrophobic silica as shown in the heat transfer suppression sheet of the third embodiment.
[0104] (Average primary particle size of nanoparticles: 1 nm or more and 100 nm or less)
[0105] When the average primary particle size of the nanoparticles is limited to a predetermined range, further higher thermal insulation properties can be obtained.
[0106] That is, when the average primary particle size of the nanoparticles is 1 nm or more and 100 nm or less, especially in a temperature range of less than 500° C., it is possible to suppress the convection heat transfer and conduction heat transfer in the heat transfer suppression sheet, and further improve the thermal insulation. In addition, even when compressive stress is applied, the gaps remaining between the nanoparticles and the contacts between the multiple particles can suppress the conduction heat transfer, and the thermal insulation of the heat transfer suppression sheet can be maintained.
[0107] It should be noted that the average primary particle size of the nanoparticles is more preferably 2 nm or more, and further preferably 3 nm or more. On the other hand, the average primary particle size of the nanoparticles is more preferably 50 nm or less, and further preferably 10 nm or less.
[0108] (Inorganic hydrate particles)
[0109] When the inorganic hydrate particles are exposed to heat from the exothermic body and reach a temperature above the thermal decomposition starting temperature, they undergo thermal decomposition, releasing their own crystal water to lower the temperature of the exothermic body and its surroundings, demonstrating a so-called "endothermic effect." In addition, after releasing the crystal water, they become porous and exhibit a heat-insulating effect through countless air pores.
[0110] Specific examples of inorganic hydrates include aluminum hydroxide (Al(OH)3), magnesium hydroxide (Mg(OH)2), calcium hydroxide (Ca(OH)2), zinc hydroxide (Zn(OH)2), iron hydroxide (Fe(OH)2), manganese hydroxide (Mn(OH)2), zirconium hydroxide (Zr(OH)2), gallium hydroxide (Ga(OH)3), etc.
[0111] For example, aluminum hydroxide has about 35% of crystal water, and as shown in the following formula, it undergoes thermal decomposition to release crystal water, exhibiting an endothermic effect. Moreover, after releasing the crystal water, it becomes a porous aluminum oxide (Al2O3), which functions as a heat insulator.
[0112] 2Al(OH)3→Al2O3+3H2O
[0113] It should be noted that, as described below, the heat transfer suppression sheet 10 of the present embodiment is suitable for being sandwiched between battery cells, for example, but in a battery cell that has thermal runaway, the temperature rises sharply to more than 200° C., and the temperature continues to rise to around 700° C. Therefore, as inorganic particles, it is preferable to be composed of an inorganic hydrate having a thermal decomposition starting temperature of 200° C. or more.
[0114] Regarding the thermal decomposition starting temperatures of the above-mentioned inorganic hydrates, aluminum hydroxide is about 200°C, magnesium hydroxide is about 330°C, calcium hydroxide is about 580°C, zinc hydroxide is about 200°C, iron hydroxide is about 350°C, manganese hydroxide is about 300°C, zirconium hydroxide is about 300°C, and gallium hydroxide is about 300°C. They all roughly overlap with the temperature range of the rapid temperature rise of the battery cell when thermal runaway occurs, and can effectively suppress the temperature rise. Therefore, they can be said to be preferred inorganic hydrates.
[0115] (Average secondary particle size of inorganic hydrate particles: 0.01 μm or more and 200 μm or less)
[0116] In addition, when inorganic hydrate particles are used as the first inorganic particles, if the average particle size is too large, it takes a certain amount of time for the first inorganic particles (inorganic hydrate) located near the center of the heat transfer suppression sheet 10 to reach their thermal decomposition temperature, so the first inorganic particles near the center of the sheet may not be completely thermally decomposed. Therefore, the average secondary particle size of the inorganic hydrate particles is preferably 0.01 μm to 200 μm, and more preferably 0.05 μm to 100 μm.
[0117] (Particles composed of heat-expandable inorganic material)
[0118] Examples of the thermally expandable inorganic material include vermiculite, bentonite, mica, and perlite.
[0119] (Particles composed of a porous body containing water)
[0120] Specific examples of the hydrous porous body include zeolite, kaolinite, montmorillonite, acid clay, diatomaceous earth, wet silica, dry silica, aerogel, mica, vermiculite and the like.
[0121] (Inorganic hollow sphere)
[0122] The heat insulating material used in the present invention may contain inorganic hollow spheres as the first inorganic particles.
[0123] When the inorganic hollow spheres are included, convection heat transfer or conductive heat transfer of heat in the thermal insulation material can be suppressed in a temperature range lower than 500° C., and the thermal insulation property of the thermal insulation material can be further improved.
[0124] As the inorganic hollow sphere, at least one selected from the group consisting of volcanic ash hollow spheres, silica hollow spheres, fly ash hollow spheres, barite hollow spheres, and glass hollow spheres can be used.
[0125] (Content of Inorganic Hollow Spheres)
[0126] The content of the inorganic hollow spheres is preferably 60% by mass or less based on the total mass of the heat transfer suppressing sheet.
[0127] (Average particle size of inorganic hollow spheres: 1 μm or more and 100 μm or less)
[0128] The average particle size of the inorganic hollow spheres is preferably 1 μm or more and 100 μm or less.
[0129] <Second Inorganic Particles>
[0130] In the case of containing 2 kinds of inorganic particles in the heat transfer inhibition sheet, the second inorganic particles are not particularly limited as long as the material, particle size, etc. are different from the first inorganic particles. As the second inorganic particles, inorganic hollow spheres such as oxide particles, carbide particles, nitride particles, inorganic hydrate particles, silicon dioxide nanoparticles, metal oxide particles, microporous particles, hollow silicon dioxide particles, particles made of thermally expandable inorganic materials, particles made of water-containing porous bodies, etc. can be used, and their details are as described above.
[0131] It should be noted that the conduction heat transfer of nanoparticles is extremely small, and even when compressive stress is applied to the heat transfer suppression sheet, excellent thermal insulation can be maintained. In addition, metal oxide particles such as titanium dioxide have a high effect of shielding radiant heat. Furthermore, if large-diameter inorganic particles and small-diameter inorganic particles are used, the small-diameter inorganic particles will enter the gaps between the large-diameter inorganic particles, thereby forming a denser structure, which can improve the heat transfer suppression effect. Therefore, when using, for example, nanoparticles as the above-mentioned first inorganic particles, it is preferred that the heat transfer suppression sheet further contain particles composed of metal oxides having a larger particle size than the first inorganic particles as the second inorganic particles.
[0132] Examples of the metal oxide include silicon oxide, titanium oxide, aluminum oxide, barium titanate, zinc oxide, zircon, zirconium oxide, etc. Titanium oxide (titanium dioxide) is a component with a higher refractive index than other metal oxides, and has a high effect of diffusely reflecting light and shielding radiant heat in a high temperature range of 500° C. or more, so titanium dioxide is most preferably used.
[0133] When at least one particle selected from dry silica particles and silica aerogel is used as the first inorganic particle and at least one particle selected from titanium dioxide, zircon, zirconium oxide, silicon carbide, zinc oxide and aluminum oxide is used as the second inorganic particle, in order to obtain excellent thermal insulation performance in a temperature range of 300° C. or less, the first inorganic particle is preferably 50% by mass or more, more preferably 60% by mass or more, and further preferably 70% by mass or more relative to the total mass of the inorganic particles. In addition, the first inorganic particle is preferably 95% by mass or less, more preferably 90% by mass or less, and further preferably 80% by mass or less relative to the total mass of the inorganic particles.
[0134] On the other hand, in order to obtain excellent thermal insulation performance in a temperature range exceeding 300° C., the second inorganic particles are preferably 5% by mass or more, more preferably 10% by mass or more, and further preferably 20% by mass or more relative to the total mass of the inorganic particles. In addition, the second inorganic particles are preferably 50% by mass or less, more preferably 40% by mass or less, and further preferably 30% by mass or less relative to the total mass of the inorganic particles.
[0135] (Average primary particle size of the second inorganic particles)
[0136] When the heat transfer suppressing sheet contains second inorganic particles composed of a metal oxide, if the average primary particle size of the second inorganic particles is 1 μm to 50 μm, radiant heat transfer can be effectively suppressed in a high temperature region of 500° C. or higher. The average primary particle size of the second inorganic particles is more preferably 5 μm to 30 μm, and most preferably 10 μm or less.
[0137] (Content of Inorganic Particles)
[0138] In the present embodiment, if the total content of the inorganic particles in the heat transfer suppression sheet 10 is appropriately controlled, the heat insulating property of the heat transfer suppression sheet 10 can be sufficiently ensured.
[0139] The total content of the inorganic particles is preferably 30% by mass or more, and more preferably 50% by mass or more, relative to the total mass of the heat transfer suppression sheet 10. In addition, if the total content of the inorganic particles is too much, the content of the fiber is relatively reduced. Therefore, in order to obtain an appropriate strength of the heat transfer suppression sheet 10, the total content of the inorganic particles is preferably 80% by mass or less, and more preferably 70% by mass or less, relative to the total mass of the heat transfer suppression sheet 10.
[0140] <Fiber>
[0141] The heat transfer suppressing sheet 10 of the present embodiment includes at least one type of fiber selected from inorganic fibers and organic fibers.
[0142] <Organic Fiber>
[0143] The organic fiber imparts flexibility to the heat transfer suppressing sheet 10 and has the effect of improving the effect of retaining the inorganic particles and maintaining the strength and shape of the sheet. As a material for the organic fiber in the heat transfer suppressing sheet 10, in addition to the single-component organic fiber, a core-sheath structured binder fiber can also be used. The core-sheath structured binder fiber has a core extending in the longitudinal direction of the fiber and a sheath formed so as to cover the outer peripheral surface of the core.
[0144] When using a single-component organic fiber or a core-sheath structured binder fiber as the material of the organic fiber, a portion of the fiber surface is melted by heating during the manufacture of the heat transfer suppressing sheet 10, and then the inorganic particles or other fibers are fused around the organic fiber by cooling. Therefore, excellent sheet strength can be obtained.
[0145] When a core-sheath structured binder fiber is used as the material of the organic fiber, the first organic material constituting the core portion and the second organic material constituting the sheath portion are described below.
[0146] (First organic material)
[0147] When a core-sheath structured binder fiber is used as the fiber, there is no particular limitation as long as the first organic material constituting the core has a higher melting point than the sheath present on the outer peripheral surface of the core, i.e., the second organic material. The first organic material may be at least one selected from polyethylene terephthalate, polypropylene, and nylon.
[0148] (Second organic material)
[0149] When a core-sheath structured binder fiber is used as the organic fiber, there is no particular limitation as long as the second organic material constituting the sheath has a lower melting point than the first organic material constituting the core. The second organic material may be at least one selected from polyethylene terephthalate, polyethylene, polypropylene and nylon.
[0150] The melting point of the second organic material is preferably 90° C. or higher, more preferably 100° C. or higher. The melting point of the second organic material is preferably 150° C. or lower, more preferably 130° C. or lower.
[0151] (Organic fiber content)
[0152] In the present embodiment, when the heat transfer suppression sheet 10 includes organic fibers, if the content of the organic fibers in the heat transfer suppression sheet 10 is appropriately controlled, the effect of improving the strength of the heat transfer suppression sheet 10 can be sufficiently obtained.
[0153] The content of organic fibers is preferably 2% by mass or more, and more preferably 4% by mass or more, relative to the total mass of the heat transfer suppression sheet 10. In addition, if the content of organic fibers is too high, the content of inorganic particles is relatively reduced. Therefore, in order to obtain the desired thermal insulation performance, the content of organic fibers is preferably 10% by mass or less, and more preferably 8% by mass or less, relative to the total mass of the heat transfer suppression sheet 10.
[0154] (Fiber length of organic fibers)
[0155] The fiber length of the organic fibers is not particularly limited, but the average fiber length of the organic fibers is preferably 10 mm or less from the viewpoint of ensuring moldability and processability.
[0156] On the other hand, from the viewpoint of improving the strength of the heat transfer suppressing sheet 10 , the average fiber length of the organic fibers is preferably 0.5 mm or more.
[0157] <Inorganic Fiber>
[0158] Since the inorganic fiber has excellent strength, it functions as the aggregate of the heat transfer suppression sheet 10 and can obtain high compressive strength. Therefore, the heat transfer suppression sheet 10 is sandwiched between the battery cells 20a, 20b, and 20c, and it does not deform significantly even if these battery cells are squeezed, and can maintain its shape. In addition, since the inorganic fiber has high high-temperature strength, it can maintain its shape even when the heat transfer suppression sheet 10 is exposed to high temperatures.
[0159] As the inorganic fiber, a single inorganic fiber can be used, or two or more inorganic fibers can be used in combination. As the inorganic fiber, for example, silica fiber, alumina fiber, aluminum silicate fiber, zirconium oxide fiber, carbon fiber, soluble fiber, refractory ceramic fiber, aerogel composite material, magnesium silicate fiber, alkaline earth silicate fiber, potassium titanate fiber, silicon carbide fiber, potassium titanate whisker fiber and other ceramic fibers, glass fiber, glass wool, slag wool and other glass fibers, rock wool, basalt fiber, mullite fiber, as mineral fibers other than the above natural mineral fibers such as wollastonite, etc. can be cited.
[0160] These inorganic fibers are preferred from the viewpoint of heat resistance, strength, availability, etc. Among the inorganic fibers, silica-alumina fibers, alumina fibers, silica fibers, rock wool, alkaline earth silicate fibers, and glass fibers are particularly preferred from the viewpoint of handleability.
[0161] The cross-sectional shape of the inorganic fiber is not particularly limited, and examples thereof include circular cross-section, flat cross-section, hollow cross-section, polygonal cross-section, core cross-section, etc. Among them, fibers with a hollow cross-section, flat cross-section or polygonal cross-section with a special cross-section can be appropriately used because they can slightly improve thermal insulation properties.
[0162] The preferred lower limit of the average fiber length of the inorganic fibers is 0.1 mm, and the more preferred lower limit is 0.5 mm. On the other hand, the preferred upper limit of the average fiber length of the inorganic fibers is 50 mm, and the more preferred upper limit is 10 mm. If the average fiber length of the inorganic fibers is less than 0.1 mm, it is not easy to cause the inorganic fibers to be entangled with each other, and the mechanical strength of the heat transfer suppression sheet may be reduced. On the other hand, if the average fiber length of the inorganic fibers is greater than 50 mm, although the reinforcing effect can be obtained, the inorganic fibers cannot be tightly entangled with each other, or only a single inorganic fiber is rolled up, which easily produces continuous gaps, and thus may cause a reduction in thermal insulation.
[0163] The preferred lower limit of the average fiber diameter of the inorganic fibers is 1 μm, the more preferred lower limit is 2 μm, and the further preferred lower limit is 3 μm. On the other hand, the preferred upper limit of the average fiber diameter of the inorganic fibers is 15 μm, and the more preferred upper limit is 10 μm. If the average fiber diameter of the inorganic fibers is less than 1 μm, the mechanical strength of the inorganic fibers themselves may be reduced. In addition, from the perspective of the impact on human health, the average fiber diameter of the inorganic fibers is preferably greater than 3 μm. On the other hand, if the average fiber diameter of the inorganic fibers is greater than 15 μm, the solid heat transfer using the inorganic fibers as a medium increases, which may lead to a decrease in thermal insulation, and the formability and strength of the heat transfer suppression sheet may be deteriorated.
[0164] (Inorganic fiber content)
[0165] In the present embodiment, when the heat transfer suppression sheet 10 contains inorganic fibers, the content of the inorganic fibers is preferably 3% by mass or more and 15% by mass or less relative to the total mass of the heat transfer suppression sheet.
[0166] In addition, the content of the inorganic fiber is more preferably 5% by mass or more and 10% by mass or less relative to the total mass of the heat transfer suppression sheet. By setting such a content, the shape retention, extrusion resistance, wind pressure resistance, and inorganic particle retention capacity based on the inorganic fiber can be well balanced. In addition, when the heat transfer suppression sheet 10 contains organic fibers and inorganic fibers as fibers, by appropriately controlling the content of the inorganic fibers, the organic fibers and the inorganic fibers are entangled with each other to form a three-dimensional network, thereby further improving the effect of retaining the inorganic particles, etc.
[0167] <Other mixed materials>
[0168] It should be noted that the heat transfer suppressing sheet of this embodiment may further contain a binder, a colorant, etc. as needed. These are useful for the purpose of reinforcing the heat transfer suppressing sheet and improving moldability, and the total amount relative to the total mass of the heat transfer suppressing sheet is preferably 10% by mass or less.
[0169] (Hot-melt powder)
[0170] As an adhesive, for example, hot-melt powder can be used. Hot-melt powder is a powder having the property of melting by heating. By making a mixture obtained by mixing materials contain hot-melt powder and heating it, the hot-melt powder melts, and when it is subsequently cooled, it solidifies in a state containing fibers and inorganic particles as materials. Therefore, the shape retention of the heat transfer suppression sheet can be improved. As the hot-melt powder, hot-melt powders with various melting points can be cited, so hot-melt powders with an appropriate melting point can be selected according to the manufacturing conditions of the heat transfer suppression sheet.
[0171] (Content of hot-melt powder)
[0172] When the mixture of the mixed materials contains hot-melt powder, even a small amount thereof can improve the shape retention of the heat transfer suppressing sheet. Therefore, the content of the hot-melt powder is preferably 0.5% by mass or more, more preferably 1% by mass or more relative to the total mass of the mixture.
[0173] On the other hand, if the content of the hot-melt powder is increased, the content of the inorganic particles and fibers will relatively decrease. Therefore, in order to obtain the desired thermal insulation performance, the content of the hot-melt powder is preferably 5% by mass or less, more preferably 4% by mass or less relative to the total mass of the mixture.
[0174] [Method for producing heat transfer suppressing sheet]
[0175] <Method for Manufacturing Heat Transfer Suppression Sheet of First Embodiment>
[0176] The following reference Figure 1 An example of a method for producing the heat transfer suppression sheet according to the first embodiment will be described.
[0177] For example, fiber (glass fiber 1), inorganic particles (titanium dioxide 3, nano silicon dioxide 4) and an unillustrated adhesive are put into a mixer such as a V-type mixer at a predetermined ratio to prepare a mixture. Thereafter, the obtained mixture is put into a predetermined mold, pressurized by a press machine, etc., the obtained molded body is heated, and then cooled to obtain a heat insulating material 9 processed into a sheet shape.
[0178] Thereafter, the heat insulating material 9 is immersed in a solution containing the liquid repellent substance 2 and then dried, thereby manufacturing the heat transfer suppressing sheet 10 having the liquid repellent substance 2 attached to the sheet surface.
[0179] In the manufacturing method of the first embodiment, the heat insulating material 9 is immersed in a solution containing the liquid repellent substance 2 and then dried. Therefore, the liquid repellent substance 2 enters between the fine inorganic particles on the sheet surface, and the liquid repellent substance 2 can be attached to the sheet surface without gaps, thereby obtaining excellent liquid repellency.
[0180] In addition, if Figure 4 As shown, when the heat insulating material 9 is formed with the pores 7 having the openings 7a, the liquid repellent substance 2 penetrates into the heat insulating material 9 through the openings 7a, and the inner wall portions of the three-dimensionally connected pores 7 are also given liquid repellency. Therefore, even if cracks occur in the area on the sheet surface to which the liquid repellent substance 2 is attached and dew condensation water 5 penetrates into the inside, the three-dimensionally connected pores 7 can suppress the penetration of dew condensation water 5 beyond that area. In addition, when the battery is used, even if dew condensation water 5 penetrates into the inside of the heat transfer suppression sheet 10 through the openings 7a, by making the inner wall portions of the pores 7 have liquid repellency, the dew condensation water 5 can be easily discharged from the openings 7a without penetrating into other parts.
[0181] <Method for Manufacturing Heat Transfer Suppression Sheet of Second Embodiment>
[0182] The following reference Figure 3 An example of a method for producing the heat transfer suppression sheet according to the second embodiment will be described.
[0183] First, fibers (glass fibers 1), inorganic particles (titanium dioxide 3, nano-silicon dioxide 4) and the like are mixed with a solution containing a liquid-repellent substance 2 at a predetermined ratio, stirred with a stirrer, and then the resulting mixed solution is dried. Thus, a mixture is obtained in which the liquid-repellent substance 2 is attached to at least a portion of the surface of the fibers and inorganic particles. Thereafter, the resulting mixture and an adhesive (not shown) are placed in a predetermined mold, pressurized with a press machine, etc., and the resulting molded body is heated and then cooled, thereby obtaining a heat transfer suppression sheet 10 processed into a sheet shape.
[0184] In the manufacturing method of the second embodiment, since the liquid repellent substance is attached to the surface of the fiber and inorganic particles as the material, even if the condensation water 5 and the like infiltrate from the surface to a certain extent, it will not completely penetrate, and the fibers and inorganic particles having the liquid repellent substance 2 attached to the surface can prevent the infiltration beyond that. Therefore, the reduction of the insulation due to the infiltration of the condensation water 5 can be prevented, and the reduction of the thermal insulation due to the infiltration of the electrolyte can be prevented by appropriately selecting the liquid repellent substance 2.
[0185] It should be noted that, as shown in the method for manufacturing a heat transfer suppressing sheet of the second embodiment, the liquid repellent material 2 is preliminarily attached to the surface of the material, and after processing it into a sheet, the liquid repellent material 2 is further attached to the sheet surface in the same manner as the manufacturing method of the first embodiment, so that the liquid repellency can be further improved.
[0186] As described above, the heat transfer suppression sheet 10 of the first and second embodiments is preferably manufactured by a dry method. When the dry method is used, at least one selected from dry silica and silica aerogel suitable for the dry method is preferably used as the inorganic particles.
[0187] <Method for Manufacturing Heat Transfer Suppression Sheet of Third Embodiment>
[0188] Hereinafter, an example of a method for producing the heat transfer suppression sheet according to the third embodiment will be described.
[0189] Fibers (glass fibers 1), liquid-repellent inorganic particles (hydrophobic silica), and a binder (not shown) are placed in a V-type mixer or other mixer at a predetermined ratio to prepare a mixture. The resulting mixture is then placed in a predetermined mold, pressurized by a press or other machine, and the resulting molded body is heated and then cooled to obtain a heat transfer suppressing sheet processed into a sheet shape.
[0190] In the manufacturing method of the third embodiment, since the inorganic particles used as the material have a liquid repellent effect, after being processed into a sheet, it is not necessary to perform a liquid repellent treatment on the material stage or the thermal insulation material processed into a sheet, and it can be easily manufactured. It should be noted that only a part of the inorganic particles used as the material can be made of hydrophobic silica and the rest can be made of other inorganic particles. Even with such a structure, a water repellent effect can be obtained.
[0191] It should be noted that, as shown in the method for manufacturing the heat transfer suppression sheet of the third embodiment, even when liquid-repellent inorganic particles are used as the liquid-repellent material 2, after processing them into a sheet, the liquid-repellent material 2 is further attached to the sheet surface by following the manufacturing method of the first embodiment, thereby further improving the liquid repellency.
[0192] <Other Manufacturing Methods>
[0193] The manufacturing method of the present invention is not particularly limited as long as it can manufacture a heat transfer suppression sheet that satisfies the conditions of the present invention. In addition to the manufacturing methods of the heat transfer suppression sheets of the first to third embodiments described above, there can be mentioned a method in which silicone, synthetic resin, etc. are attached to the surface of oxide particles as inorganic particles, and liquid repellent treatment is applied before use. Furthermore, a heat transfer suppression sheet having liquid repellency can be manufactured by the same method as the manufacturing method of the heat transfer suppression sheet of the third embodiment.
[0194] (Heating temperature)
[0195] When a core-sheath structured binder fiber is used as the fiber, since the melting point of the first organic material constituting the core is higher than the melting point of the second organic material constituting the sheath, when the mixture is heated, a heating temperature is selected that allows the core to be left and the sheath to melt. If the heating temperature is appropriately adjusted in this way, after cooling, other fibers and inorganic particles can be covered on the outer peripheral surface of the core, the inorganic particles can be retained, and a three-dimensional and strong skeleton can be formed. As a result, the overall shape of the heat transfer suppression sheet can be further maintained with high strength.
[0196] (Thickness of heat transfer suppression sheet)
[0197] The thickness of the heat transfer suppression sheet of this embodiment is not particularly limited, and is preferably 0.05 mm or more and 10 mm or less. If the thickness is 0.05 mm or more, sufficient compressive strength can be obtained while ensuring thermal insulation. On the other hand, if the thickness is 10 mm or less, the desired size as a battery pack can be achieved.
[0198] [Battery Pack]
[0199] An example of a battery pack to which the heat transfer suppressing sheet 10 according to an embodiment of the present invention is applied is as described above. Figure 2 Here, we use Figure 2 The structure and effect of the battery pack are described in detail. It should be noted that, as mentioned above, Figure 2 The heat transfer suppressing sheet 10 shown may also be replaced with other heat transfer suppressing sheets within the scope of the present invention.
[0200] like Figure 2 As shown, the battery pack 100 includes a plurality of battery cells 20a, 20b, and 20c and a heat transfer suppressing sheet according to the present embodiment, and the plurality of battery cells are connected in series or in parallel.
[0201] For example, Figure 2As shown, the heat transfer suppression sheet 10 of this embodiment is interposed between the battery cells 20a and 20b, and between the battery cells 20b and 20c. The battery cells 20a, 20b, 20c and the heat transfer suppression sheet 10 are further housed in a battery case 30.
[0202] In addition, the heat transfer suppressing sheet 10 is as described above.
[0203] In the battery pack 100 constructed in this way, when the temperature of a battery cell repeatedly rises and cools and condensation water 5 is generated on the surface of the battery cell, the heat transfer suppression sheet 10 that can prevent the penetration of moisture is present between the battery cells, thereby preventing short circuits between the battery cells.
[0204] In addition, if the temperature of a battery cell rises significantly and damage occurs due to expansion, if the liquid-repellent material attached to the heat transfer suppression sheet 10 is appropriately selected, the infiltration of the leaked electrolyte can be suppressed, thereby preventing a chain reaction of thermal runaway caused by the infiltration of high-temperature electrolyte.
[0205] In the battery pack of this embodiment, the heat transfer suppression sheet 10 disposed between the battery cells 20a, 20b, 20c and the battery case 30 may be in contact with the battery cells or may have a gap therebetween. However, if there is a gap between the heat transfer suppression sheet 10 and the battery cells 20a, 20b, 20c, deformation of the battery cells can be tolerated even when the temperature of any one of the plurality of battery cells rises and the volume expands.
[0206] It should be noted that the heat transfer suppression sheet 10 of this embodiment can be made into various shapes according to its manufacturing method. Therefore, it can cope with any shape without being affected by the shape of the battery cells 20a, 20b, 20c and the battery case 30. Specifically, in addition to square batteries, it can also be applied to cylindrical batteries, flat batteries, etc.
[0207] Various embodiments have been described above, but the present invention is certainly not limited to such examples. Those skilled in the art can certainly think of various variations or modifications within the scope described in the claims, and it should be understood that they also belong to the technical scope of the present invention. In addition, the various constituent elements in the above embodiments can also be arbitrarily combined within the scope of the invention without departing from the gist of the invention.
[0208] It should be noted that the present application is based on the Japanese patent application (Japanese Patent Application No. 2022-103045) filed on June 27, 2022, and its contents are incorporated herein by reference.
[0209] Explanation of symbols
[0210] 1. Fiberglass
[0211] 2 Liquid-repellent substances
[0212] 3. Titanium dioxide
[0213] 4 nanometer silicon dioxide
[0214] 5. Condensation
[0215] 6. Organic Fiber
[0216] 7 empty holes
[0217] 7a Opening
[0218] 8 water inlet / drainage channels
[0219] 9,19 Insulation materials
[0220] 10Heat transfer suppression sheet
[0221] 14Inorganic particles
[0222] 20a, 20b, 20c battery cells
[0223] 30 battery case
[0224] 100 battery pack
Claims
1. A heat transfer suppression sheet, which is a heat transfer suppression sheet sandwiched between a plurality of battery cells, characterized in that: The heat transfer suppressing sheet includes at least one fiber selected from inorganic fibers and organic fibers, and a liquid repellent substance having a surface tension smaller than that of water. 2 . The heat transfer suppressing sheet according to claim 1 , comprising inorganic particles, at least a part of the inorganic particles being the liquid repellent substance.
3. The heat transfer suppressing sheet according to claim 2, wherein: The liquid-repellent substance is hydrophobic silica.
4. The heat transfer suppressing sheet according to claim 1, wherein: The heat transfer suppressing sheet comprises inorganic particles, The liquid repellent substance adheres to at least a part of the surface of the heat transfer suppression sheet, the surface of the inorganic particles inside the heat transfer suppression sheet, and the surface of the fibers inside the heat transfer suppression sheet.
5. The heat transfer suppressing sheet according to claim 4, wherein: The liquid repellent substance is at least one selected from paraffin base oils, cycloparaffin base oils, hydrocarbon synthetic oils, ester synthetic oils, animal and plant oils and fats, silicone resins, fluororesins, rosin-based sizing agents, and alkyl ketene dimer sizing agents.
6. The heat transfer suppressing sheet according to claim 4, wherein: The inorganic particles are particles composed of at least one inorganic material selected from oxide particles, carbide particles, nitride particles, and inorganic hydrate particles.
7. The heat transfer suppressing sheet according to claim 6, wherein: The inorganic particles include at least one particle selected from the group consisting of dry silica particles and silica aerogels.
8. The heat transfer suppressing sheet according to claim 7, wherein: The inorganic particles further include particles of at least one selected from the group consisting of titanium dioxide, zircon, zirconium oxide, silicon carbide, zinc oxide, and aluminum oxide.
9. The heat transfer suppressing sheet according to claim 1, wherein: The liquid-repellent substance has a surface tension smaller than a surface tension of an electrolyte contained in the battery cell.
10. The heat transfer suppressing sheet according to claim 9, wherein: The surface tension of the liquid repellent substance is 45 mN / m or less.
11. The heat transfer suppressing sheet according to claim 10, wherein: The liquid-repellent substance is at least one selected from silicone resin and fluororesin.
12. The heat transfer suppressing sheet according to claim 1, wherein: The heat transfer suppression sheet has a plurality of three-dimensionally connected pores, and the pores open toward the surface of the heat transfer suppression sheet. 13 . A battery pack comprising a plurality of battery cells and the heat transfer suppressing sheet according to claim 1 , wherein the plurality of battery cells are connected in series or in parallel.
Citation Information
Patent Citations
Heat insulation sheet for battery pack and battery pack
JP2021034278A
Liner base paper
JP2022103045A